(untitled) (Jurnal Pertanian Terpadu, 2020)
This research aims to compare the physical properties of soil in agroforestry land use and secondary dryland forest in Wuno Sub-watershed, Sigi Regency. The research method uses a survey method followed by sampling for analysis materials in the laboratory. Soil analysis was carried out at the Laboratory of Soil Science, Faculty of Agriculture, Tadulako University. Determination of the location for the sampling of the soil was determined purposively (purposive sampling) to obtain 6 sample points. Soil samples were taken 3 times for each land use. The results showed that the soil texture on agroforestry land had a sand fraction (12.6-67.2%), then a dust fraction (19.1%), and a clay fraction (1.1%), and secondary dryland forest had a fraction of sand (12.6-67.2%) 18.1-43.9%), dust fraction (37.2%), and clay fraction (0.8%). The highest permeability at a depth of 0-20 cm was found in agroforestry land 10.44 cm/hour, and the lowest in secondary dryland forest was 2.29 cm/hour. Soil mass density in agroforestry land is 1.41 g/cm3, the secondary dryland forest is 1.64 g/cm. The soil porosity in the agroforestry section was 40.85%, while the secondary dryland forest was 22.90%. Soil organic matter in agroforestry land is 4.23%, while the secondary dryland forest is 3.81%.